Spectrum of pediatric gliomas: implications for the development of future therapies. Issue 12 (December 2007) - Pytel, Peter
The therapy of gliomas is still challenging. This is especially true for pediatric gliomas because response to conventional cytotoxic chemotherapy agents and radiation therapy is currently often poor and because therapy-related morbidity is a significant problem in children. Stratification of tumors according to biologic characteristics and new more targeted therapies therefore hold the promise of better tumor control as well as reduced side effects. Significant progress has been made in recent years in understanding the biology of gliomas. These new insights into the molecular mechanism driving tumor growth uncover new potential molecular targets for future therapies. In addition, they start to uncover biologically defined tumor subtypes that may have to be considered independently in the search for optimal treatment regimens.